Defining the transition from new to normal: a qualitative investigation of the clinical change process - Santana R. Silver; Kayla Christine Jones; Kimberly Hook; Erika L. Crable; Emily R. George; Janet R. Serwint; Kirsten Austad; Allan Walkey; Mari-Lynn Drainoni (BMC Health Services Research)
Abstract Background Understanding how and when a new evidence-based clinical intervention becomes standard practice is crucial to ensure that healthcare is delivered in alignment with the most up-to-date knowledge. However, rigorous methods are needed to determine when a new clinical practice becomes normalized to the standard of care. To address this gap, this study qualitatively explores how, when, and why a clinical practice change becomes normalized within healthcare organizations. Methods We used purposive sampling to recruit clinical leaders who worked in quality improvement and/or implementation science in diverse health contexts. Enrolled participants completed semi-structured interviews around implementing evidence-based practices. Qualitative data was inductively and deductively analyzed, and was guided by a modified version of the Normalization Process Theory (NPT) framework to identify salient themes. Additionally, identified normalization strategies were mapped to the Expert Recommendations for Implementation Change (ERIC) project. Results A total of 17 individuals were interviewed. Two categories of themes emerged: 1) signals of when a new clinical practice is considered to be normalized within clinical care; and 2) strategies utilized to normalize new clinical innovations. Participants described four key signals for identifying when a novel clinical practice becomes the new normal: 1) integrated seamlessly into existing workflows; 2) scaled across the entire organizational unit; 3) has strong staff buy-in and ownership; and 4) no longer needs monitoring and evaluation to be sustained. Major strategies to normalize new clinical interventions included: 1) taking a patient approach that starts slow and gains momentum; 2) identifying and using methods to gain staff buy-in and ownership; and 3) conducting ongoing measurement of progress towards normalization. Conclusions The results offer valuable insight into the indicators that signify when a novel clinical practice becomes normalized, and the strategies employed to facilitate this transition. These findings can inform future research to develop instruments that implementation leaders can use to systematically measure the clinical change process.